Auctions of failed banks: an analysis of losing bidders - Tim Zhou (Review of Quantitative Finance and Accounting, 2023)
Between 2007 and 2013, the Federal Deposit Insurance Corporation (FDIC) used purchase and assumption (P&A) as a resolution method to auction 492 failed institutions to healthy banks. While existing studies reveal positive value effects on winning bidders of these auctions, this study finds that losing bidders experience negative abnormal stock returns. Furthermore, the losing bidders’ stockholders react negatively to a worsening market condition and an increased probability of failure. The returns, nevertheless, are related to the market power gains and distorted competitive condition post-auction. These results raise concerns that this type of intervention potentially gives rise to anticompetitive behavior among participating banks of FDIC auctions.